(untitled) (Research, Society and Development, 2021)
Introduction: Fatal familial insomnia (FFI) is a neurodegenerative autosomal dominant prion disease caused by a mutation in the cellular protein gene (PrPC). The aim of this review is to identify the initial clinical manifestations of FFI and its geographic distribution during the last decade. Methodology: This is a systematic literature review which includes case reports about FFI, published from 2011 to 2021, indexed in PubMed/MEDLINE databases. Results: Forty-nine individuals with FFI were detected. The most common initial symptoms were progressive insomnia (55%), cognitive deficits (25%), weight loss (25%), gait alterations (25%) and disorientation (25%). Some cases presented symptoms suggestive of other diagnostic hypotheses such as tremors (15%) and mood changes (10%). The USA presented an absolute frequency of 17 people distributed in three families. China had a total of ten affected by FFI in five families. Brazil, Germany and South Korea had two affected families each country. However, regarding the total number of FFI carriers, Brazil had seven, but South Korea, France and Spain had three carriers each country. Conclusion: China and the USA have the highest FFI absolute frequencies, yet some European countries, such as Spain and France, have a higher relative frequency. Although insomnia is the most common initial symptom, there are cases which FFI may initially manifest with symptoms that mimic other neurodegenerative pathologies or psychological pathologies, difficulting the diagnosis.